PERBANDINGAN KINERJA KEUANGAN BANK SYARIAH DAN BANK KONVENSIONAL DI INDONESIA (STUDI KASUS PADA PT. BANK MUAMALAT DAN PT. BANK MANDIRI) - mardewi, putri; Mansyur, fakhruddin; Nuhung, Mahmud (Universitas Muhammadiyah Makassar, 2019)
This research aims to compare the financial performance of Bank Muamalat and Bank Mandiri in Indonesia in the 2011-2015 period using financial ratios. The financial ratio used consists of CAR, ROA, LDR, NPL, and BOPO. The data used in this study is obtained from the Published Financial Reports issued by each of the Banks concerned. The analysis technique used to see a comparison of the financial performance of Bank Muamalat and Bank Mandiri is a comparative research method that is comparative in nature. The analysis conducted shows that there are significant differences for each financial ratio between Bank Muamalat and Bank Mandiri in Indonesia. Bank Muamalat has better performance in terms of LDR and BOPO ratios, while Bank Mandiri has better performance in terms of CAR, ROA and NPL ratios.